Chinese student migration and integration in the UK: an exploration of links to and engagement with local communities in Nottingham - Wu, Bin (Centre on Migration, Policy and Society, 2014)
The unprecedented growth in the number of Chinese students in the last decade or so has raised challenging issues about their integration on campus and in the wider community. Many questions arise regarding the impact of Chinese student migration and integration in local communities: To what extents has Chinese student migration in the past reshaped the landscape of diasporic Chinese community in the UK? What progresses have Chinese students made in terms of integration in local communities? And what are key factors or features which may be related or contribute to different statuses of integration among Chinese students? To address above questions, a local community perspective has been posed and tested by combining official data (UK Censuses 2001, 2011, HESA's international student statistics) and our questionnaire survey conducted in Nottingham in the summer of 2013. The results from data analysis shed new light on the importance ofcivic engagement in Chinese student integration. Based upon the survey information, furthermore, four types of integration strategies or statuses are distinguished according to the scope of student social networking whilst relevant background factors, features and impacts are recognised.